Evaluasi Media APE dari Kardus Bekas dalam Pengenalan Huruf Hijaiyah pada Anak PAUD - Fatimah Uri; Rian Vebrianto (Journal on Education, 2025)
The introduction of hijaiyah letters is an important stage in early childhood learning, especially to build a foundation for Al-Qur'an literacy. This study aims to evaluate the effectiveness of using educational teaching aids (APE) made from used cardboard in introducing hijaiyah letters to PAUD children. The methodology used in this research is Research and Development (R&D) involving 26 teachers where the data collection process is taken directly by researchers using an instrument in the form of a media assessment Google form which explains the media and then asks respondents to answer and assess the quality of the media. . The data obtained was analyzed using descriptive analysis. The research results show that the value of the learning media components assessed by the teacher is ((X) ̅= 4.48, SD= 0.0586), and the value is more than the mean, namely 4.37 to 4.63. This shows that this media is worthy of use, with noted improvements in aspects of design and durability. This research concludes that APE media from used cardboard has great potential as an innovative and sustainable learning tool for introducing hijaiyah letters to PAUD children.